A New Potential Threat for Nosocomial Infections: Cupriavidus metallidurans as a Cause of Bacteremia in Children - Fahri Yüce Ayhan; Utku Karaarslan; Mustafa Gülderen; Özgen Alpay Özbek; Aybüke Akaslan Kara; Gizem Güner Özenen; Hasan Ağın (Galenos Publishing House, 2024)
Hospital infections associated with uncommon pathogens usually originated from environmental sources and are challenging for microbiologists and clinicians because of the difficulties in the differentiation of colonization vs infection. Increasing reports of bacteremia caused by environmental pathogens point out their importance in hospital infections. The increasing number of case reports of bacteremia due to Cupriavidus spp., impose to consider these unusual microorganisms which are aerobic Gram-negative rods that live in soil and water. In this report, we present two cases of bacteremia in which Cupriavidus metallidurans were isolated from blood cultures and discuss the roles of the isolates in hospital infection.